Cariotipo de la especie invasora Pterois volitans (Scorpaeniformes: Scorpaenidae) de Isla Margarita Island, Venezuela - Nirchio, Mauro; Ehemann, Nicolás; Siccha-Ramirez, Raquel [UNESP]; Ron, Ernesto; Eduardo Pérez, Julio; Rita Rossi, Anna; Oliveira, Claudio [UNESP] (Universidad de Costa Rica, 2014)
The genus Pterois includes nine valid species, native to the Red Sea and Indian Ocean throughout the Western Pacific. P. volitans and P. miles are native to the Indo-Pacific, and were introduced into Florida waters as a result of aquarium releases, and have been recently recognized as invaders of the Western Atlantic and Caribbean Sea (Costa Rica to Venezuela). Thus far, cytogenetic studies of the genus Pterois only cover basic aspects of three species, including P. volitans from Indo-Pacific Ocean. Considering the lack of more detailed information about cytogenetic characteristics of this invasive species, the objective of the present study was to investigate the basic and molecular cytogenetic characteristics of P. volitans in Venezuela, and compare the results with those from the original distribution area. For this, the karyotypic characteristics of four lionfish caught in Margarita Island, Venezuela, were investigated by examining metaphase chromosomes by Giemsa staining, C-banding, Ag-NOR, and two-colour-Fluorescent in situ hybridization (FISH) for mapping of 18S and 5S ribosomal genes. Comparing the sequences of the 16S gene of the specimens analyzed, with sequences already included in the Genbank, we corroborated that our specimens identified as P. volitans are in fact this species, and hence exclude the possibility of a misidentification of P. miles. The diploid number was 2n=48 (2m+10sm+36a) with FN=60. Chromosomes uniformly decreased in size, making it difficult to clearly identify the homologues except for the only metacentric pair, and the pairs number two, the largest of the submetacentric series. C-banding revealed only three pairs of chromosomes negative for C-band, whereas all remaining chromosomes presented telomeric and some interstitial C-positive blocks. Only two chromosomes were C-banding positive at the pericentromeric regions. Sequential staining revealed Ag-NOR on the tips of the short arms of chromosome pair number two and the FISH assay revealed that 18S rDNA and 5S rDNA genes are co-located on this chromosome pair. The co-localization of 5S rDNA and 45S rDNA is discussed. Both constitutive heterochromatin and NOR location detected in samples examined in this study, differ from those reported for P. volitans in previous analysis of specimens collected in Indian Ocean (Java), suggesting the occurrence of chromosome microrearrangements involving heterochromatin during the spread of P. volitans.
Karyotype of the invasive species Pterois volitans (Scorpaeniformes: Scorpaenidae) from Margarita Island, Venezuela
Keywords: 16S rRNA mitochondrial gene; 18S and 5S ribosomal genes; Invasive species; Karyotype; Molecular identification